Glossary of Biomechanical Terms, Concepts, and Units - Rodgers, M. M.; Cavanagh, P. R.
SECTION 1 KINEMATICS- The Description of Motion SECTION 2 FORCES SECTION 3 KINETICS - The Study of the Forces that Cause Motion SECTION 4 COMPUTATIONAL METHODS SECTION 5 MUSCLE MECHANICS SECTION 6 MECHANICS OF MATERIALS SECTION 7 INSTRUMENTATlON SECTION 8 BODY SEGMENT VARIABLES SECTION 9 UNITS SECTION 10 Index To Terms